AJARAN BERUMAH TANGGA DALAM SERAT CANDRARINI KARYA RANGGAWARSITA (TINJAUAN SOSIOLOGI SASTRA) - Indraswari Pikatan (Universitas Muhammadiyah Surakarta, 2012)
The problems of the study cover the structure of Serat Candrarini by Ranggawarsita, the tenets of Serat Candrarini on the life of the Javanese women, and the relevance of the tenets to the life of the Javanese women at present.The method used in this research was descriptive qualitative. Serat Candrarini represents the main data source. The poem was taken by using purposive sampling technique based on specific criteria. To validate the data, he study used data triangulation. The data-collecting techniques were library research, observation and document. The technique of analyzing data used was content analysis. The conclusion of the study is that the structure of SCR consisted of both extrinsic and intrinsic structures. Extrinsic structures covered sound, rhythm, diction and figurative language. The intrinsic of CSR included theme, feeling, tone, and message. The main tenets in SCR included: taking care of oneself, maintaining the house- hold, forgiving, faithful, sincere, speaking nicely, modesty, sense of belonging, dressing up, loyal to parents in-law, and women as educator in the family.